2015
DOI: 10.1103/physreve.91.033008
|View full text |Cite
|
Sign up to set email alerts
|

Advanced dynamic-equilibrium model for a nanobubble and a micropancake on a hydrophobic or hydrophilic surface

Abstract: The dynamic-equilibrium model for stabilization of a nanobubble on a hydrophobic surface by Brenner and Lohse [M. P. Brenner and D. Lohse, Phys. Rev. Lett. 101, 214505 (2008)] has been modified taking into account the van der Waals attractive force between gas molecules inside a nanobubble and solid surface. The present model is also applicable to a nanobubble on a hydrophilic surface. According to the model, the pressure inside a nanobubble is not spatially uniform and is relatively higher near the solid surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 60 publications
1
54
1
1
Order By: Relevance
“…They are preferably formed on hydrophobic, rough surfaces, 209 but also occur on hydrophilic substrates. [210][211][212] According to a popular school of thought on their stability, the three-phase contact line is fixed on the substrate by a strong pinning mechanism. Some scientists have even used the term superstability, since the surface bubbles do not seem to be affected by shockwaves 213 and temperatures near the boiling point of water.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…They are preferably formed on hydrophobic, rough surfaces, 209 but also occur on hydrophilic substrates. [210][211][212] According to a popular school of thought on their stability, the three-phase contact line is fixed on the substrate by a strong pinning mechanism. Some scientists have even used the term superstability, since the surface bubbles do not seem to be affected by shockwaves 213 and temperatures near the boiling point of water.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…For a given gas oversaturation ζ > 0, there exists an equilibrium in which the outflux of gas molecules from the nanobubble due to the large Laplace pressure is compensated by the influx into the bubble due to gas oversaturation, i.e., there is no net flux. Though the flux of gas particles out or into the nanobubble is not spatially uniform along the interface as shown by Weijs et al [25] and Yasui et al [26], the net flux integrated over the whole interface is zero. The contact angle of the surface nanobubble is not given by Young's equation, but determined by the equilibrium,…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that this UFB exists stably for over 1 month [1]. However, the mechanism by which UFB stabilizes in the water remains to be unknown, and several theories have been proposed [1][2][3][4][5][6][7][8][9][10], but a clear mechanism has not yet been established in reality.…”
Section: Introductionmentioning
confidence: 98%